2019
DOI: 10.1177/0972150919879299
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Paradigm Shift in Strategy of M&As in India in a Volatile Period Through Motive Analysis: Evidences from the IT Industry

Abstract: The reform period in India led to corporate restructuring, including mergers and acquisitions (M&As). Specifically, the reform process helped the Indian information technology (IT) sector to gain a competitive edge. With the gain in competitive edge, IT companies experienced the foreign-led rapid organic and inorganic growth. However, the subprime crisis of 2008–2009 not only caused a decline in inorganic investment but also caused a shift in preference from the international sector to the domestic sector.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In such cases, count models such as the standard Poisson and negative binomial (NB) are used (Wooldridge, 2006, p. 649), and in the case of the overdispersion of the dependent variable, as in our case, NB model is preferred to the Poisson model (Cameron & Trivedi, 2005; Greene, 2008; Ismail & Jemain, 2007; Linden & Mantyniemi, 2011). This is in line with the previous studies with similar nature of the dependent variable (Blanchard et al, 2008; Camarero et al, 2020; Singla, 2019; Soni et al, 2019; Varma et al, 2015, 2017; Wilson & Desire, 2013).…”
Section: Control Variablessupporting
confidence: 93%
See 1 more Smart Citation
“…In such cases, count models such as the standard Poisson and negative binomial (NB) are used (Wooldridge, 2006, p. 649), and in the case of the overdispersion of the dependent variable, as in our case, NB model is preferred to the Poisson model (Cameron & Trivedi, 2005; Greene, 2008; Ismail & Jemain, 2007; Linden & Mantyniemi, 2011). This is in line with the previous studies with similar nature of the dependent variable (Blanchard et al, 2008; Camarero et al, 2020; Singla, 2019; Soni et al, 2019; Varma et al, 2015, 2017; Wilson & Desire, 2013).…”
Section: Control Variablessupporting
confidence: 93%
“…A case in point is the Indian IT industry. Soni et al (2019) observe that Indian IT companies went for cross-border M&A between 2000 and 2015 with the prominent motive of gaining competitive edge as well as surviving in the volatile period arising from subprime crisis. In addition, the factors that contributed to an increase in M&A activity in this sector were reform processes in India and globalisation; availability of Internet and web-based developments in 1995–1996; entry of foreign players and diversification of established players due to huge potential for growth (Kar, 2011); country-specific comparative advantages such as availability of cheap, abundant, dynamic, and young labour; English language skills; strategic time zone (Popli et al, 2016; Sun et al, 2012); and firm-specific advantages related to product design and project management skills (Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kalra et al (2013 examined the firm-specific factors impacting M&As for the Indian banking sector and found the absence of any significant impact of M&As on their financial performance. As per the findings of Soni et al (2019), the economic recession of 2008-2009 was found to significantly reduce the M&A activities by Indian IT companies for the time period 2000-2015. The reduction in M&As activities was more in international deals than domestic deals after the subprime crisis, and the increase in the share of the market-seeking motive for domestic market reflects the fact that Indian IT companies looked inward for the market in the volatile period after the crisis (Kar & Soni, 2018).…”
Section: Overview Of Literaturementioning
confidence: 65%
“…Extant literature suggests the effects of various macroeconomic factors (Bhasin et al, 2020), international shocks (like the South-East Asian crisis in 1997, recession caused by the financial crisis in 2008, etc) (Kar et al, 2020;Soni et al, 2019) and firm-specific strategic reasons having impacted M&As in India (Kalra et al, 2013;Kar & Soni, 2018). Although, investigating the impacts of these factors on Indian M&As is beyond the scope of this study, yet our trend analysis reveals three significant peaks generated in the years 1999, 2000 and 2011. This may be attributed to those factors.…”
Section: Analysis Of Trends Of Mergers and Acquisitionsmentioning
confidence: 77%
“…Another important revelation is that after the crisis, Indian IT companies needed to enhance its capability and cost-effectiveness to remain competitive in the volatile scenario. So, companies, focussing within India, went for more deals for strategic asset seeking and efficiency seeking motives rather than market seeking motive (Soni, Kar, & Bhasin, 2019). Further, Investment for efficiency enhancement helped Indian IT companies to gain a competitive edge which is in sync with the argument of Bhattacharjee and Chakrabarti (2015).…”
Section: Results For Financial Performance Parametersmentioning
confidence: 99%